Penerapan Model Pembelajaran Kooperatif Tipe MAM (Make A Match) terhadap Kemampuan Berpikir Kreatif Siswa Kelas III MI Al-Muhsin 1 Krapyak - Yatimah, Durrotun; Sukati, Sukati; Maksum, Khanif (Alma Ata University Press, 2024)
This research is motivated by the learning has not been varied, the interest in learning owned by third grade students of MI Al-Muhsin 1 is still low so that it affects the ability to think creatively. The learning of MI Al-Muhsin 1 Krapyak has never applied the cooperative learning model of make a match type, especially on theme 8 subtheme 1 lesson 2 of Ppkn subject The purpose of this research is to: 1) Describe the application of cooperative learning model of make a match type in creative thinking ability of third grade students of MI Al-Muhsin 1 Krapyak; 2) Knowing the application of cooperative learning model of make a match type can improve the creative thinking ability of third grade students of MI Al-Muhsin 1 Krapyak.This research is a quantitative research with quasi-experimental type. The population of this research was all third grade students of MI Al-Muhsin 1 Krapyak with 20 students of class IIIA (experimental class) and 20 students of class IIIB (control class). Sampling is by simple random sampling or random sample, data collection techniques with test and observation techniques. The results showed that; 1) The application of cooperative learning model of make a match type to the creative thinking ability of third grade students of MI Al-Muhsin 1 Krapyak is running smoothly in accordance with the lesson plan that the creative thinking ability of students obtained pre test value 100% (20 people) students think creatively with good category and post test value obtained 85% (17 people) students have creative thinking ability.Keywords: learning model, make a match, creative thinking